PENGARUH WAKTU HIDROTERMAL DAN TMAOH DALAM SINTESIS LANGSUNG MCM-41 - Mustofa Ahda; Sutarno Sutarno; Eko Sri Kunarti (Pharmaciana, 2015)
The MCM-41processing synthesis with variation time hydrothermal and TMAOH at directsynthesis process has been done. The synthesis of MCM–41 was used templating agents withcetiltrimetilammonium bromide (CTAB). The optimization of synthesis of MCM-41 was carried outto produce good material characteristics. Hydrothermal time variation performed in the synthesis ofMCM-41 for 18 hours, 24 hours, 48 hours and 88 hours has been done. So the study of effect TMAOHwas used CTAB/ TMAOH ratio: 1 and 1.25. The results showed that the 24- hour time hydrothermalwas able to produce the good crystallinity with 100% relative crystallinity. However, the best stabilityof MCM-41 materials synthesized in hydrothermal time during the 48 hours. So the effect ofTMAOH additions in the synthesis MCM-41 can bedecreased crystallinity of MCM-41.